Dietary Acid Load but Not Mediterranean Diet Adherence Score Is Associated With Metabolic and Cardiovascular Health State: A Population Observational Study From Northern Italy - Sanz, Juana Maria; Sergi, Domenico; Colombari, Simona; Capatti, Eleonora; Situlin, Roberta; Biolo, Gianni; Di Girolamo, Filippo Giorgio; Lazzer, Stefano; Šimunič, Boštjan; Pišot, Rado; Passaro, Angelina (Frontiers in Nutrition, 2022)
Diet plays a pivotal role in shaping the trajectory to chronic diseases. In this regard, the Mediterranean diet has been widely shown to exert beneficial effects on cardio-metabolic health. On the contrary, the Western diet, which has also been reported to be an acidogenic dietary pattern, elicits detrimental effects on both metabolic and cardiovascular health. However, the role of dietary acid load as a predictor of cardio-metabolic prognosis remains to be elucidated. Thus, this study aims at comparing the adherence to the Mediterranean diet (MDA) and dietary acid load (DAL) focusing on their relationship with metabolic and cardiovascular prognosis. Four hundred forty-eight individuals aged 55-80 years were grouped depending on their MDA, assessed using food frequency questionnaires or DAL evaluated by Potential Renal Load Acid (PRAL) and net-endogenous acid production (NEAP). Study participants underwent anthropometric and biochemical measures. Metabolic syndrome (MetS) prevalence was evaluated according to National Cholesterol Education Program Adult-Treatment-Panel III. Finally, the cardiovascular (CV) risk was evaluated using three independent algorithms: AtheroSclerotic Cardiovascular Disease (ASCVD), European Systematic COronary Risk Evaluation (SCORE) and Cuore risk scores. MDA was negatively associated with PRAL and NEAP. Individuals in the higher MDA tertile had higher HDL-cholesterol as well as lower HOMA-IR and fat mass relative to the lowest MDA tertile. However, in the high-MDA tertile group there was not a significantly lower MetS prevalence nor cardiovascular risk. Instead, both the MetS prevalence and cardiovascular risk were higher in individuals in the higher acid PRAL quartile relative to the lower alkaline PRAL quartile. DAL, especially assessed by PRAL, but not MDA was associated with indices of metabolic and cardiovascular prognosis. Thus, DAL assessed by 24-h dietary recalls may represent a better predictor of cardio-metabolic health if compared to MDA evaluated using food frequency questionnaires.